2021
DOI: 10.1016/j.clnu.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary diversity changes and mortality among older people: A prospective cohort study

Abstract: Background & aims: The association between dietary diversity (DD) changes and mortality remains unclear. We aimed to investigate the association between DD changes and all-cause mortality among older people. Methods: A total of 17,959 participants with a mean age of 84.8 years old were enrolled at baseline. Food groups were collected at baseline and follow-up using simplified food frequency questionnaire (FFQ), and then overall, plant-based and animal-based dietary diversity score (DDS) were calculated. DDS ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…Based on the randomly assigned centenarians’ code numbers, the predefined sex was determined to obtain comparable numbers of women and men for each age group. Detailed descriptions of the study design and data quality assessment have been provided in previous publications [ 31 , 32 ]. At each follow-up period, information on diet, lifestyle and medical history was updated through face-to-face interviews using structured questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the randomly assigned centenarians’ code numbers, the predefined sex was determined to obtain comparable numbers of women and men for each age group. Detailed descriptions of the study design and data quality assessment have been provided in previous publications [ 31 , 32 ]. At each follow-up period, information on diet, lifestyle and medical history was updated through face-to-face interviews using structured questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked how often these foods were consumed, and the dietary information was recorded as frequent (≥5 times/week), occasional (1–4 times/week) or rare (<1/week). Considering the frequency of food consumption, we counted the number of food groups to measure the DDS, the nine food groups were given a score of 0 (rare), 1 (occasional) and 2 (frequent) without considering a minimum intake for the food groups [ 32 , 35 ]. Thus, the score of overall DDS, plant-based DDS (including fresh vegetables, preserved vegetables, fresh fruit, tea, garlic and food made from beans) and animal-based DDS (including meat, fish and eggs) was calculated based on a scale of 0–18, 0–12, and 0–6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported that regardless of how the participants’ DDS changed, e.g., from low to medium or high scores, from medium to high scores, or from high to medium or low scores, the individuals maintaining high scores (13–18 points) had a lower mortality risk. The results shows that a highly diverse diet throughout several years is associated with a lower mortality risk at ages ≥ 65 years [ 61 ]. However, this study did not have a follow-up time long enough to allow the population to be 100 + years and thus does not provide information regarding if this association persists among individuals reaching 100 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A diet diversity score (DDS) was calculated assigning 1 point per food group consumed 1-4 times/week and 2 points per food group consumed ≥ 5 times/week, allowing scores ranging from 0-18 points. Subsequently the [75] relation between changes in DDS and mortality was investigated [61]. The authors reported that regardless of how the participants' DDS changed, e.g., from low to medium or high scores, from medium to high scores, or from high to medium or low scores, the individuals maintaining high scores (13-18 points) had a lower mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were required to recall their frequency of intake and portion size consumed during the past 12 months. The FFQ was derived and modified from the validated Chinese dietary FFQ from the Chinese Center for Disease Control and Prevention (41,42), which was widely used in various studies (43)(44)(45)(46)(47)(48). Previous studies suggested that the reproducibility and validity of the Chinese dietary FFQ were satisfactory and it can be used to classify the subjects according to their food consumption in 1 year (41,42).…”
Section: Questionnaire Collectionmentioning
confidence: 99%